Kelekatan Orangtua dan Kecerdasan Sosial pada Remaja Pondok Pesantren Modern - Nurjanah Nurjanah; Adi Heryadi (Lembaga Penelitian Universitas YARSI, 2020)
This study aims to determine the relationship between the attachment of parents to the social intelligence of adolescent Miftahunnajah Modern Islamic Boarding School. Social intelligence becomes a very important thing because basically humans cannot live alone. Many activities in an individual's life are related to others. The many social phenomena that occur illustrate the increasingly eroding social intelligence in society. Weakening social sense and empathy also occur among adolescents.The research subject was students of the Modern Miftahunnajah Islamic Boarding School with the criteria of adolescents aged 10-22 years. The number of subjects in this study were 112 students. The sampling technique in this study used a simple random sampling. Data collection uses a scale that has been tested for validity and reliability. The scale of parental attachment in this study was based on three aspects of stickiness, namely trust, communication and alienation, which amounted to 41 items. The scale of social intelligence in this study is based on two aspects of social intelligence, namely social awareness and social facilities totaling 30 items. From the hypothesis test, it is known that the correlation coefficient (pearson correlation) is 0.376 and the significance level is 0.000. The significance level is smaller than 0.05 (p 0.05) so that it can be said that there is a significant relationship between the attachment of parents and social intelligence. The coefficient of determination on the two variables shows R square of 0.121 or equal to 12.1%. This value shows the effective contribution of parental attachments that contribute to parental intelligence is equal to 12.1% and 87.9% social intelligence is influenced by other factors